2015
DOI: 10.1002/jssc.201500816
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the chiral separation of novel diazenes

Abstract: Two new types of potential liquid-crystalline azo compounds were synthesized in the form of racemic mixtures and as the individual S enantiomers. Both materials consisting of two substituted aromatic rings in the molecular core and one chiral center at the aliphatic moiety showed mesomorphic behavior. The separation of the R and S enantiomers by chiral high-performance liquid chromatography was unsuccessful when the azo compounds were in their natural E state. However, the irradiation of the compounds in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
1
11
1
Order By: Relevance
“…This report represents our continuous effort to reach sufficient enantiomeric separation for newly synthesized LCMs containing a diazene moiety. Recently, we have demonstrated that individual enantiomers of these simple materials could be partially separated in normal phase separation mode after irradiation by UV light and that the resolution could be significantly improved by applying RP separation mode . The photoinduced isomerization phenomenon for the above mentioned relatively simple structures and its consequence on chromatographic behavior and UV spectra have been discussed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This report represents our continuous effort to reach sufficient enantiomeric separation for newly synthesized LCMs containing a diazene moiety. Recently, we have demonstrated that individual enantiomers of these simple materials could be partially separated in normal phase separation mode after irradiation by UV light and that the resolution could be significantly improved by applying RP separation mode . The photoinduced isomerization phenomenon for the above mentioned relatively simple structures and its consequence on chromatographic behavior and UV spectra have been discussed.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned in Section 1, the irradiation of diazene moiety‐containing materials with photons of the appropriate wavelength initiates the transition of the respective compound from the more stable E isomeric form to the thermodynamically labile Z isomeric form. The time needed for reaching the photostationary state was studied for liquid crystals 1 and 2 utilizing achiral chromatography similar to the procedure described in with an MP composed of a mixture of toluene/methanol, 99.5:0.5 v/v. Table summarizes the relative amounts of the E and Z isomers of liquid crystals 1 and 2 at specific times.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations